IS Ideology: Debunking its Pseudo-Religious Character - Mohamed Ali (2017)
The recent arrest of two Singaporeans under the Internal Security Act (ISA) highlights the pivotal role IS ideology plays in current radicalisation processes. The key to effectively challenge IS propaganda is to invalidate its claim of religious legitimacy.